PARTICULARIDADES ELEMENTARES DO USO DE MEDICAMENTOS CONTROLADOS EM CRIANÇAS COM TRANSTORNO DE ESPECTRO AUTISTA-TEA. (REMUNOM, 2024)
The use of medication in autistic children is a subject of great importance and complexity, requiring a careful and well-founded approach. This work addresses the use of controlled medications in autistic children, an issue of great relevance and complexity. By analyzing various aspects, it will be possible to understand the importance, benefits and potential risks associated with the use of these medications in this specific group of patients. Autism Spectrum Disorder (ASD), a complex neurodevelopmental condition that concerns communication, social interaction and behavior, and which requires a multidisciplinary and integrated approach for its diagnosis and therapeutic treatment. The study explores the main dimensions of ASD, including definitions, diagnostic criteria, prevalence, therapeutic interventions and advances in multidisciplinary approaches.